Patterns and processes of invasive grass impacts on wildlife in Australia - A. C. Grice; Eric P. Vanderduys; Justin J. Perry; Garry D. Cook (Wildlife Society Bulletin)
ABSTRACT There are almost 400 naturalized grass species in Australia and most terrestrial and many freshwater ecosystems are subject to invasion by one or more species. Some species can dominate the ground stratum of the vegetation and thus radically transform the structure, composition and ecological functioning of the ecosystem. In these situations, the species richness of the herbaceous vegetation typically declines as the grasses out‐compete native grasses and forbs for water, nutrients, and light. In terrestrial environments, invasive grasses often modify disturbance regimes, especially the frequency and intensity of fire. These effects on vegetation structure and composition and water and nutrient cycling are habitat‐altering for the fauna of the invaded systems. Although some wildlife species do well in vegetation transformed by invasive grasses, there are many negative effects on wildlife through reduced resource availability and unsuitable fire regimes. There are few cost‐effective, broad‐scale options for reversing the effects of invasive grasses on radically transformed systems. © 2013 The Wildlife Society.